Global Standing of EPN for Insect Pest Management vis-a-vis Indian Contribution: The Missing Links (Indian Journal of Nematology, 2024)
Entomopathogenic nematodes (EPNs) provide a quick, reliable and environmentally safe mode for controlling insect pests. Focused research in the US and Europe has led to a fast-growing global market of EPN-based products in the past couple of decades. The global revenues of EPN products match the returns from Beauveria, Metarhizium and Trichoderma. Although EPNs are considered to be broad spectrum, their tremendous international success is due to products that target specific stages of a specific pest in a specific crop in a specific agro-climatic region. Targeted products are launched in cruiser and ambusher EPNs to manage sedentary and mobile pests, respectively. The EPN products are largely available in the form of wettable powder and water-dispersible granules with six to ten months of shelf-life under refrigerated conditions. Unfortunately, indigenous products do not match up to international standards and therefore, do not contribute to the fast-growing international market. Several products are marketed with unrealistic claims on their shelf-life. The powder formulations are developed without adequate technical knowledge of the survival mechanism of EPNs, and invariably anhydrobiosis is not induced in these. The development of formulations by untrained EPN specialists is a major factor why our products do not meet the international quality parameters, and storage and shipment stability. Only trained nematologists having sound knowledge of the survival strategy of EPNs and an understanding of the biochemical processes involved in the inducement of anhydrobiosis should handle product development. Majority of the local products are non-selective to the pest, crop or geographical location. A one-size-fits-all approach to the promotion of EPN products defies the concept of niche specificity and insect-specificity. Field application should be synchronous with the biology and behaviour of the target pest. Scientists must understand and integrate insect behaviour and soil dynamics.